2019
DOI: 10.1111/jop.12815
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting prognosis in locoregional recurrence of oral squamous cell carcinoma

Abstract: Background Recurrence of oral squamous cell carcinoma (rOSCC) after primary treatment is associated with poor survival outcomes. Salvage treatment with further surgery, radiotherapy and chemotherapy has high morbidity, making patient selection crucial. However, in the recurrence setting, reliable stratification data are scarce. Decision‐making in this context is consequently complex. We investigated factors influencing overall survival after rOSCC. Methods Retrospective cohort study of patients with rOSCC (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…Similarly, Matsuura et al found shorter survival times (OS and DFS) in patients with nodal involvement in the primary resection [ 20 ]. Consistent with previous reports [ 13 , 19 , 21 ], we found that positive resection margins had a negative impact on OS in patients with recurrent disease.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, Matsuura et al found shorter survival times (OS and DFS) in patients with nodal involvement in the primary resection [ 20 ]. Consistent with previous reports [ 13 , 19 , 21 ], we found that positive resection margins had a negative impact on OS in patients with recurrent disease.…”
Section: Discussionsupporting
confidence: 93%
“…We found that several factors—N+ neck, PNI, LVI, ENE, and positive surgical margins—were associated with disease recurrence, a finding that is consistent with previous reports [ 11 , 12 , 13 , 14 , 15 ]. In our sample, 108 patients developed disease recurrence a mean of 20.8 months after primary treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There seem to be no gender differences in this association. Besides serving as the risk factors of OC, smoking and drinking have also been identified as adverse prognostic factors of OC (Borsetto et al., 2019; Feghali et al., 2019). Areca nut (AN), the main component of betel quid (BQ), has been classified as a human carcinogen by the International Agency for Research on Cancer (Dave, Trivedi, & Adhvaryu, 1992) and identified as an independent risk factor for OC (Chen et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The overall 5-year survival rate of oral cancer is only 62% as against 89% and 99% for breast and oral cancers, respectively (Gupta et al 2016 ). Additionally, the recurrence of human oral cancer further adds to the problem (Borsetto et al 2019 ). Hence, it is need of the hour to look for the alternative approaches for the management of oral cancer.…”
Section: Introductionmentioning
confidence: 99%